2019
DOI: 10.1002/nop2.234
|View full text |Cite
|
Sign up to set email alerts
|

Family members' beliefs and attitudes towards visiting policy in the intensive care units of Ghana

Abstract: Aim This study aimed to investigate family members' beliefs and attitudes towards the visiting policies of intensive care units (ICUs). Design It employed a descriptive cross‐sectional quantitative design. Method This study recruited four public hospitals in Ghana with a sample of 200 family members. The study was conducted using a self‐administered questionnaire. The data were collected and analysed with SPSS version 16. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…All this has been confirmed in studies that have detected several stressful factors in an intensive care environment, such as fear of unknown consequences, disruption of routine, lack of familiarity with the environment, and emotional upheavals 41 , 42 . Visits by relatives in the ICU are fundamental because they generate satisfaction and awareness for the family members 43 .…”
Section: Discussionmentioning
confidence: 99%
“…All this has been confirmed in studies that have detected several stressful factors in an intensive care environment, such as fear of unknown consequences, disruption of routine, lack of familiarity with the environment, and emotional upheavals 41 , 42 . Visits by relatives in the ICU are fundamental because they generate satisfaction and awareness for the family members 43 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Ghana, Yakubu et al reported family skepticism when given the opportunity for unrestricted visitation, with concerns that it could hinder recovery. 27 Important additional factors must also be considered when interpreting our findings, namely professional staffing and infrastructure. Open family presence at the bedside can be challenging to ICU staff.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings suggest that FCC intervention has positive effects on reducing ICU delirium prevalence. The majority of included studies increased family visiting time or controlled the visiting times flexibly (Eghbali‐Babadi et al., 2017 ; Gan Xiaoqing et al., 2017 ; Rosa et al., 2019 ), which can engage ICU patients with their family members longer time, enable them to fully feel the support of relatives and friends and facilitate adaptation to environmental changes (Garrouste‐Orgeas et al., 2016a ; Yakubu et al., 2019 ). In addition, the targeted training, memory induction and avoidance of sensory deprivation provided by family members (Eghbali‐Babadi et al., 2017 ; Mitchell et al., 2017 ) may improve patients’ perception of the environment, relieve fear and alleviate tension and anxiety (Piao et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Frequent communication generates a better family understanding of the healthcare process and families can receive timely and accurate information, thus meeting their information needs and effectively participating in decision‐making (Hönig & Gündel, 2016 ). In addition, it promotes family participation in the living care of patients, relatives may feel a sense of usefulness and self‐worth since they contribute to patients’ rehabilitation process (Kang et al., 2020 ; Wong et al., 2019b ; Yakubu et al., 2019 ). Thus, medical staff should raise awareness of the important role of family members in patients’ rehabilitation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation